Investigative biotechniques for evaluation of the mammary gland of production animals - Sombra, Thaíse; Nunes-Pinheiro, Diana (Pubvet, 2020)
The implementation of new techniques to evaluate the mammary gland reveals the diagnosis and prognosis of the main changes affecting the udder, thus resulting in a reduction of producers’ economic losses and a consequent increase in animal welfare. In vivo and in vitro techniques help, individually or jointly, the early detection of changes in mammary gland structures in the main production animals, by adding pertinent and necessary semiological information in the identification of the problem and its consequent solution. With a focus on minimizing milk yield and quality losses in high-yielding animals, avoiding infant feeding disorders and starvation death, and preventing mammary gland diseases that corroborate the lack of welfare of these animals. Thus, the implementation of mammary gland investigation techniques opens new perspectives for studies involving the mammary environment in different perspectives, in order to diagnose and institute the best therapy to be used.